Niklas Luhmann's concept of communication — semiotic consequences of a redefinition of the notion of social unity - Grácio, Ricardo (2014)
The reformulation system’s theory performs in the concept of communication attributes it a new centrality in the field of the theory of society and in the forms of its reading and structural interpretation. Its around it that we propose a reflection about the status and context of social semiotics descriptive ambitions as a project of comprehension of the social. In a context of increasing transformation, this very ambition is subjected to conditionings that undermine its value as social critic, as well as its capacity to mobilize programs of social transformation. The path taken leads to a group of observations concerning the meaning of social semiotics itself in the context of contemporary functionally differentiated society.